1994
DOI: 10.1016/0043-1648(94)90115-5
|View full text |Cite
|
Sign up to set email alerts
|

A model of the dynamics of boundary film formation

Abstract: The dynamics of formation and loss of the boundary films formed during sliding on steel surfaces were investigated over a range of temperature. Tests are performed on a cylinder-on-disk machine using mineral oil with various concentrations of zinc dial~ldithiophosphate (ZDP). The thickness and refractive index of the boundary films during step load test were monitored in situ with an ellipsometer, and the composition of the films was analyzed by X-ray photoelectron spectroscopy (XPS). As temperature increases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Our results provide evidence that un-reacted ZDDP (which aligns with peak 2 (figure 1)) decreases significantly when the concentration of ZDDP is decreased from 1.2 to 0.3%. Current U.S. environmental laws regulate maximum P content in passenger vehicles to 0.1%, resulting in a ZDDP concentration of $1% [18], which has also been found to be close to the optimum ZDDP concentration range for the AW regime [55]. Chao et al [55] has suggested that increasing ZDDP concentrations promote thicker films, which are also formed more rapidly.…”
Section: Total Electron Yieldmentioning
confidence: 95%
See 1 more Smart Citation
“…Our results provide evidence that un-reacted ZDDP (which aligns with peak 2 (figure 1)) decreases significantly when the concentration of ZDDP is decreased from 1.2 to 0.3%. Current U.S. environmental laws regulate maximum P content in passenger vehicles to 0.1%, resulting in a ZDDP concentration of $1% [18], which has also been found to be close to the optimum ZDDP concentration range for the AW regime [55]. Chao et al [55] has suggested that increasing ZDDP concentrations promote thicker films, which are also formed more rapidly.…”
Section: Total Electron Yieldmentioning
confidence: 95%
“…Current U.S. environmental laws regulate maximum P content in passenger vehicles to 0.1%, resulting in a ZDDP concentration of $1% [18], which has also been found to be close to the optimum ZDDP concentration range for the AW regime [55]. Chao et al [55] has suggested that increasing ZDDP concentrations promote thicker films, which are also formed more rapidly. In addition, he suggested that lower concentrations of ZDDP will lead to significantly less adsorption on the surface, resulting in the formation of shorter chain polyphosphates.…”
Section: Total Electron Yieldmentioning
confidence: 95%
“…For example, the effect of various concentrations of ZnDDP in mineral oil using a cylinder-on-disk machine operating at 0.06 m/s was studied by Choa et al [62]. It was found that the removal of protective surface films is thought to depend on decreasing film durability rather than reduction of the hydrodynamic fluid film thickness caused by decreasing lubricant viscosity.…”
Section: Film Formation and Removal Models-the Role Of Oxide Layersmentioning
confidence: 99%
“…This heat transfer results in preheating of the lubricant and aggravating its localized decomposition within the contact. Progressive changes in friction coefficient during scuffing have also been observed [29]. This seems to be further evidence of a period which lasts several revolutions of rotation during which nascent surface spreads over the contacting surfaces.…”
Section: Effects Of Catalytic Decomposition Of a Lubricantmentioning
confidence: 60%
“…Thus in a high speed contact, rotating at many revolutions per second, a high areal concentration of nascent surface may therefore rapidly develop based on a lifetime of each portion of the nascent surface of several revolutions. On the other hand in slower speed laboratory scuffing tests, a distinct progression from low friction to high friction characteristic of scuffing has been observed [29]. A low speed scuffing model has been proposed where a backward flow of heat from the contact centre to the film inlet is significant and affects scuffing [30].…”
Section: Effects Of Catalytic Decomposition Of a Lubricantmentioning
confidence: 99%